Economic assessment of environmental impact in the course of oil field development and production; IOP Conference Series: Earth and Environmental Science; Vol. 27 : Problems of Geology and Subsurface Development - Tsibulnikova M. R. Margarita Radievna (Petroleum Engineering Economics. Mining Law, 2015)
Title screen